ANALYSIS OF SEXUAL HEALTH EDUCATION ON THE PERCEPTIONS OF ADOLESCENT WOMEN ON FREE SEX - Putri Eka Sejati; Elfa Puspitaningrum; Vera Wabeke; Panjarut Laisuwannachart (Universitas STRADA Indonesia, 2022)
The lack of health education to teenager about free sex affects young women's perceptions that are not good about free sex. The purpose of this study was to analyze the effect of sexual health education on adolescent girls' perceptions of free sex. The research design used pre-experimental research with one group pre-test-post-test design. The sample of this study was some young women aged 15-21 years, as many as 42 people. Based on the results of the study, it showed that of the 42 respondents, most of the respondents before being given health education had a sufficient perception of free sex. Almost all respondents have a good perception of free sex. The conclusion of this study is that there is an effect of sexual health education on the perception of young women about free sex in Sindang Baru Village, Toili District, Banggai Regency.